Circular RNAs Involve in Immunity of Digestive Cancers From Bench to Bedside: A Review - Chen, Chunyue; Xia, Congcong; Tang, Hao; Jiang, Yirun; Wang, Shan; Zhang, Xin; Huang, Tao; Yuan, Xiaoqing; Wang, Junpu; Peng, Li (Frontiers in Immunology, 2022)
The immune system plays a complex role in tumor formation and development. On the one hand, immune surveillance can inhibit the growth of tumors; on the other hand, immune evasion of tumors can create conditions conducive for tumor development and growth. CircRNAs are endogenous non-coding RNAs with a covalently closed loop structure that are abundantly expressed in eukaryotic organisms. They are characterized by stable structure, rich diversity, and high evolutionary conservation. In particular, circRNAs play a vital role in the occurrence, development, and treatment of tumors through their unique functions. Recently, the incidence and mortality of digestive cancers, especially those of gastric cancer, colorectal cancer, and liver cancer, have remained high. However, the functions of circRNAs in digestive cancers immunity are less known. The relationship between circRNAs and digestive tumor immunity is systematically discussed in our paper for the first time. CircRNA can influence the immune microenvironment of gastrointestinal tumors to promote their occurrence and development by acting as a miRNA molecular sponge, interacting with proteins, and regulating selective splicing. The circRNA vaccine even provides a new idea for tumor immunotherapy. Future studies should be focused on the location, transportation, and degradation mechanisms of circRNA in living cells and the relationship between circRNA and tumor immunity. This paper provides a new idea for the diagnosis and treatment of gastrointestinal tumors.